Językowo-kulturowo-symboliczna zaduma nad północnokresowym kultem zmarłych utrwalonym w badaniach polskich uczonych różnych pokoleń - Katarzyna Węgorowska (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2011)
The paper contains philological reflections on the cult of the dead in northeastern Borderlands. The cult has been a source of inspiration for interdisciplinary studies of many Polish scholars – the popularizers of Polish culture, tradition and folklore. The analysis of the excerpts of the works of Oskar Kolberg, Aleksander Brückner, Aleksander Lubicz, Zenon Sobierajski, Czesław Pietkiewicz, Barbara Ogrodowska, Hanna Żyburtowicz and Teresa Kokocińska, the authors of Encyklopedia Kresów, as well as of Piotr Grochowski, allows the author to emphasize the uniqueness of: a) Radunica (celebrated in the time of Easter and Whitsunday) and b) Dziady (celebrated at end of October or at the beginning of November at the time of Christmas and Shrovetide). Językowo-kulturowo-symboliczna zaduma nad północnokresowym kultem... [207] The early Slavic pagan elements of these holidays are still present in Easter and Christmas customs. The names of the objects used in rites in northeastern cemeteries, churches and houses have been interpreted in terms of language forms and symbolism. Amongst the objects, most significant are: egg, knish (a baked or fried dumpling made of flaky dough with filling), kutia (a sweet dish usually made of wheat grain, poppy seeds and honey), kisiel owsiany (oat gelatin dessert), fish, groats, pea, broad been, bread, cheese, salt, honey, poppy seeds, dried mushrooms, white tablecloth, fire, open window and door, spoon and figures of forefathers-beggars. A comprehensive analysis of the names allows the author to interpret the cult as a form of peculiar dialogue between sacrum and profanum, paganism and Christianity, the past and the present.